Implementation of carceral medicaid suspension and enrollment programs: perspectives of carceral and medicaid leaders - Sachini Bandara; Brendan Saloner; Hannah Maniates; Minna Song; Noa Krawczyk (Health & Justice)
Abstract Background Medicaid expansion via the Affordable Care Act, more recent legislation and Medicaid 1115 waivers offer opportunity to increase health care access among individuals involved in the carceral system. Effective enrollment of new beneficiaries and temporary suspension and reactivation of existing Medicaid benefits upon release is key to the success of these efforts. This study aims to characterize how jails, prisons and Medicaid agencies are implementing Medicaid suspension and enrollment programs and identifies barriers and facilitators to implementation. Methods We conducted 19 semi-structured interviews with 36 multi-state leaders in carceral facilities, Medicaid agencies, local health departments and national policy experts from 2020 to 2021. Interviews covered 4 domains: (1) the role of policy in influencing carceral and reentry Medicaid practices, (2) implementation strategies to suspend and enroll incarcerated individuals into Medicaid, (3) barriers and facilitators to successful implementation, and (4) variation in implementation between jails and prisons. Results Participants identified logistical challenges with suspension and enrollment, including limited infrastructure for data sharing between carceral facilities and Medicaid agencies, burdensome bureaucratic requirements, and challenges with Medicaid renewal, particularly in the jail environment. They offered opportunities to overcome barriers, such as the creation of specialized incarcerated Medicaid benefit categories and provision of in-reach services via managed care organizations. Participants also called for improvements to Medicaid reactivation processes, as even when facilities successfully suspended benefits, individuals faced significant challenges and delays reactivating benefits upon release. Participants also called for further loosening of the Medicaid Inmate Exclusion Policy. Discussion Findings highlight the need to update data sharing infrastructure, which will be critical to the implementation of the 1115 waivers, as carceral facilities will be subject to Medicaid billing and reporting requirements. In addition to investing in the ability to newly enroll and suspend Medicaid benefits, attention towards improving timely reactivation practices is needed, particularly given the highly elevated risk of mortality immediately after release. Participants calls for further reforms to the Medicaid Inmate Exclusion Policy are consistent with proposed legislation. Conclusions Findings can critically inform the successful implementation of Medicaid-based reforms to improve the health of incarcerated and formerly incarcerated people.